Filtering Quasi-Yagi Strip-Loaded DRR Antenna With Enhanced Gain and Selectivity by Metamaterial - Yan-Hui Ke (IEEE Access, 2021)
This paper presents a design approach of broadband filtering quasi-Yagi DRR Antenna using a strip-loaded dielectric ring resonator (DRR) and near-zero-index (NZI) metamaterial (NZIM). The ring strip is loaded to the inside wall of the DRR so that the TE01δ and TE21δ modes of the DRR can be close. Meanwhile, they function as a dual-mode magnetic dipole (M-dipole) driver and can be differentially excited at the same time for designing a wideband quasi-Yagi antenna. Benefiting from the dual-mode operation of the strip-loaded DRR, the end-fire gain across the operating band of the antenna is stable with preliminary bandpass filtering characteristics. To improve the in-band gain and enhance the filtering capability, a new coplanar NZIM with wideband NZI characteristic and dual transmission notches in the lower and upper stopbands of the preliminary gain passband, is introduced and put in the front of the DRR driver. To verify the proposed design concept, an X-band filtering quasi-Yagi antenna with the NZIM is fabricated and measured. Good agreement between the simulated and measured results can be observed. The wideband antenna has a measured -10 dB impedance bandwidth of about 16% (8.5 - 10 GHz). Within it, the peak gain of antenna reaches 8.3 dBi and 1-dB gain fractional bandwidth is about 10.8%. Meanwhile, it exhibits good gain bandpass response due to the transmission notches of the NZIM.